2004
DOI: 10.1536/jhj.45.977
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Atorvastatin Treatment on the Fibrinolytic System in Dyslipidemic Patients

Abstract: SUMMARYStatins have pleiotrophic effects related to the pathogenesis of atherosclerosis and thrombogenicity of the vessel wall beyond lipid lowering. The aim of the present study was to examine the effect of atorvastatin treatment on the fibrinolytic system in patients with dyslipidemia.The investigation was carried out on 41 dyslipidemic patients (21 males and 20 females) with a mean age of 53.8 years (range, 30-76). The patients were divided into subgroups according to their cholesterol and triglyceride leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…This result is consistent with most studies which showed a cholesterol-independent association between pre-treatment with statins and sICH in acute stroke nonthrombolysed patients, therefore suggesting pro-fibrinolytic and anti-thrombotic effects of statins [7,[16][17][18][19][20][21][22][23]29]. Only Meier et al found an independent association between prior statin use and sICH in patients treated with thrombolysis [16].…”
Section: Statin Use and Symptomatic Intracerebral Hemorrhagesupporting
confidence: 90%
See 1 more Smart Citation
“…This result is consistent with most studies which showed a cholesterol-independent association between pre-treatment with statins and sICH in acute stroke nonthrombolysed patients, therefore suggesting pro-fibrinolytic and anti-thrombotic effects of statins [7,[16][17][18][19][20][21][22][23]29]. Only Meier et al found an independent association between prior statin use and sICH in patients treated with thrombolysis [16].…”
Section: Statin Use and Symptomatic Intracerebral Hemorrhagesupporting
confidence: 90%
“…Several experimental studies demonstrated that statin use up-regulates tissue plasminogen activator (tPA) and reduces the activity of plasminogen activator inhibitor 1 (PAI)1 [16][17][18]. Moreover, there is evidence from experimental and clinical studies suggesting that statins act directly via anti-coagulant and antiplatelet mechanisms [7,[19][20][21][22][23].…”
Section: Statin Use Functional Outcome and Neurological Improvementmentioning
confidence: 99%
“…Statins were found to not only reduce blood lipids, but through their pleiotrophic effects also positively influence antithrombotic/anti-inflammatory properties of the blood vessel walls [28,29]. However, the benefit for these approaches has only been shown after a longer period of time, typically 2.5 years and more.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that the impact of atorvastatin on PAI‐1 levels is dependent on the actual type of population under study. Both Goicoechea and Orem indicated, however, that this was actually not the case with regard to the population with chronic kidney disease or mixed‐type hyperlipidaemia, whereas Davidson et al reported that in his study population, atorvastatin treatment increased PAI‐1 by 36% within a 12‐month follow‐up [31–33]. It is hard to determine univocally the impact of other statins on the markers of fibrinolytic activity.…”
Section: Discussionmentioning
confidence: 93%